ANALISIS HUBUNGAN HARAPAN DAN KENYATAAN TERHADAP TINGKAT KEPUASAN SISWA SD ISLAM AL HILAL BEKASI - Utami, Sri; Madya Ramdani, Panji (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2019)
Education Quality is of special concern to all parties. The school management is always concerned about the needs of students who support the creation of success targets in print graduation with high-intellectual student results and good personality. Variables that trigger success is the basis for the researchers to measure the level of student satisfaction by testing the influence of desired expectations with the reality of students perceived. The use of these variables can solve the problems that occurred at Al Hilal Islamic Elementary School (SD Islam Al Hilal).The sample of this research is Islamic elementary student Al Hilal, a number of 61orang. The analysis technique used is hypothesis test using t-statistic to test the partial regression coefficient and f-statistic to test the significance of influence together with level of significance 5%. In addition, the classical assumption test included normality test, multicollinearity test, and heteroscedasticity test. The result of analysis shows that the relation between expectation and reality perceived by student have positive and significant effect to student's satisfaction.This research is motivated by the development of Al Hilal Foundation by establishing Islamic Junior High School AL Hilal. Therefore SD Islam Al Hilal need to pay attention to factors such as hope and reality of students who have followed the learning process by measuring the level of satisfaction from the management of Al Hilal. From the calculation result, expected expectation variable and reality experienced have significant influence to student's satisfaction